Two-phase flow instabilities of forced circulation at low pressure in a rectangular mini-channel. (July 2016) - Yu, Zhiting; Yuan, Hongsheng; Chen, Chong; Yang, Zhida; Tan, Sichao
Highlights: Flow instabilities in a rectangular mini-channel were experimentally investigated. DWO, PDO and Ledinegg instability (LED) were found during the experiment. PDO observed in this work was not accompanied by CHF (dryout). DWO was determined by the relation between external forces and surface tension. Abstract: An experimental study has been carried out in a rectangular mini-channel to investigate the two-phase flow instabilities of a forced flow at low pressure. The inlet mass flux is gradually reduced by decreasing the rotational speed of the primary pump until the flow becomes unstable, while maintaining all other thermal parameters including system pressure, inlet temperature and heat flux unchanged. Three types of flow instabilities, density wave oscillation (DWO), pressure drop oscillation (PDO) and Ledinegg instability (LED) are identified during the experiment. The onset of flow instability (OFI) is determined by the demand curves and shows good agreement with Roach and Stoddard's correlations. The OFI is consistent with the boiling incipience and saturated condition. The stability map is obtained on the plane of subcooling number ( Nsub ) and phase change number ( Npch ). DWO and PDO occur at the region between the outlet steam quality xe = −0.001 and xe = 0.012, while the LED region becomes narrow with increasing subcooling. Finally, the mechanisms of flow instabilities in our experiment are analyzed. The results show that the PDO observed in this work is not accompanied by CHF (dryout) which is supposed to be the most common phenomenon of flow instabilities in mini-/micro-channels. DWO occurrence is determined by the relation between external forces (gravitational force and pump driving force) and surface tension. As the external forces are dominant, Type-I DWO at low outlet steam quality (DWOI ) occurs. However, with reduction of the inlet mass flux, the surface tension begins to play a dominant role. Thus Type-II DWO at high outlet quality (DWOII ), which is expected in most ordinarily sized channels, has not been observed during this work.